Potensi Aktivitas Antioksidan Ekstrak Etanol Kering dan Segar Daun Mahkota Dewa (Phaleria macrocarpa) - Sirumapea Sirumapea; Hilma; Herlina H (Journal of Indah Science and Clinic, 2022)
Compounds that function as free radical scavengers are known as antioxidants, which inhibit the oxidation process of chemical reactions and work by taking an electron to reduce the negative effects of these free radicals. The Mahkota Dewa plant (Phaleria macrocarpa), a member of the Thymelacaccae family, is known to have potential as a natural antioxidant.Various treatments prior to the extraction process of the Mahkota Dewa leaf affect the level of antioxidant activity was observed to have an effect on Both groups of leaves were extracted by maceration after part of the leaves were air-dried and partially extracted from fresh leaves. Yields were determined and phytochemical and antioxidant tests used the 1,1-diphenyl-2-picryhydrazyl method and gallic acid as a comparison. Test results showed yield values ??of 13.6% w/w (dried extract) and 9% w/w (fresh leaves). Mahkota dewa leaves contain alkaloids, flavonoids and phenolic active compounds. An antioxidant activity (IC50) value was obtained at 108.05 ppm (dried leaves). 90.97 ppm (fresh leaf) and 4.04 ppm (comparison compound). Fresh leaf sample extracts have higher antioxidant activity values ??than dried leaf sample extracts.